Protein quality of soy and the effect of processing: A quantitative review - van den Berg, Lisa A.; Mes, Jurriaan J.; Mensink, Marco; Wanders, Anne J. (Frontiers in Nutrition, 2022)
There is a growing demand for plant-based protein-rich products for human consumption. During the production of plant-based protein-rich products, ingredients such as soy generally undergo several processing methods. However, little is known on the effect of processing methods on protein nutritional quality. To gain a better understanding of the effect of processing on the protein quality of soy, we performed a quantitative review of in-vivo and in-vitro studies that assessed the indispensable amino acid (IAA) composition and digestibility of varying soy products, to obtain digestibility indispensable amino acids scores (DIAAS) and protein digestibility corrected amino acid scores (PDCAAS). For all soy products combined, mean DIAAS was 84.5 ± 11.4 and mean PDCAAS was 85.6 ± 18.2. Data analyses showed different protein quality scores between soy product groups. DIAAS increased from tofu, soy flakes, soy hulls, soy flour, soy protein isolate, soybean, soybean meal, soy protein concentrate to soymilk with the highest DIAAS. In addition, we observed broad variations in protein quality scores within soy product groups, indicating that differences and variations in protein quality scores may also be attributed to various forms of post-processing (such as additional heat-treatment or moisture conditions), as well as study conditions. After excluding post-processed data points, for all soy products combined, mean DIAAS was 86.0 ± 10.8 and mean PDCAAS was 92.4 ± 11.9. This study confirms that the majority of soy products have high protein quality scores and we demonstrated that processing and post-processing conditions can increase or decrease protein quality. Additional experimental studies are needed to quantify to which extent processing and post-processing impact protein quality of plant-based protein-rich products relevant for human consumption.